2010
DOI: 10.1016/j.pain.2010.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral processing of pain in school-aged children with neonatal nociceptive input: An exploratory fMRI study

Abstract: Due to maturation-related plasticity of the developing nociceptive system, neonatal nociceptive input, as induced by medical procedures in the neonatal intensive care unit (NICU), may cause long-term alterations in pain processing. Using functional magnetic resonance imaging, this study investigated the cerebral pain response in school-aged children and adolescents (11-16 yr) with experience in a NICU after preterm (or=37 weeks gestational age, N=9) as com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
3
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(93 citation statements)
references
References 90 publications
4
84
3
1
Order By: Relevance
“…Recent clinical follow up studies have demonstrated that in adulthood, former preterm children display altered pain threshold (Hermann et al, 2006;Hohmeister et al, 2010;Walker et al, 2009) and decreased modulatory pain mechanisms (Goffaux et al, 2008). Ten year-old former preterm infants rate medical-related pain pictures as more intense that other pain pictures, indicating that they may have more pain memories than age-matched full term infants (Grunau et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Recent clinical follow up studies have demonstrated that in adulthood, former preterm children display altered pain threshold (Hermann et al, 2006;Hohmeister et al, 2010;Walker et al, 2009) and decreased modulatory pain mechanisms (Goffaux et al, 2008). Ten year-old former preterm infants rate medical-related pain pictures as more intense that other pain pictures, indicating that they may have more pain memories than age-matched full term infants (Grunau et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…When exposed to tonic heat, preterm children exhibited significant activation in brain regions not activated in controls. Moreover, those preterm infants that received analgesia exhibited a markedly smaller loss of brain matter than controls [28] .…”
Section: Discussionmentioning
confidence: 88%
“…Two retrospective cohort studies found that both preterm and term children with NICU experience displayed greater sensitization to tonic heat [23,28] . When exposed to tonic heat, preterm children exhibited significant activation in brain regions not activated in controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2B) [79; 82] and produced a different fMRI pattern of cerebral activation in preterm children 9-14 years post NICU. [83] In addition, fewer EP adolescents tolerated a cold pressor test, with earlier withdrawal of the hand from an ice water bath (Fig. 2C) [198].…”
Section: Analgesia and Sedation In Nicumentioning
confidence: 99%